The Effect of Surfactant Characteristics on IFT to Improve Oil Recovery in Tempino Light Oil Field Indonesia - Swadesi, Boni; Marhaendrajana, Taufan; Mucharam, Leksono; Siregar, H.P. Septoratno (Journal of Engineering and Technological Sciences, 2015)
Water injection has been employed in the Tempino oil field since 1996. The current oil recovery factor is 35% of OOIP. Even though the pressure is still high, the oil production rate has declined rapidly and the water cut is approaching 89%. In order to mobilizeÂ  theÂ  oil from theÂ  reservoirÂ  more effectively, surfactant flooding is one of the solutions that can reduce residual oil saturation. Interaction between crude oil and compatible surfactant generates microemulsion,Â  as an indication of low interfacial tension. Hence the oil is expected to move out of the pore throat easily. In this research, thirty types of surfactantsÂ  were evaluated. The hydrophilicÂ  lipophilicÂ  balance (HLB)Â  was calculated andÂ  theÂ  interfacial tension (IFT)Â  with theÂ  reservoir fluidÂ  was measured. HLB criteria were established as an indicator of low IFT, which was then tested for Berea core flooding. The results indicate that an HLB between approximately 2.7 and 3.1 (on Daviesâ Scale) or greater than 11.5 (on Griffinâs Scale) givesÂ  low IFTÂ  (~10-3 dynes/cm).Â  This characteristicÂ  is possesed by surfactantÂ  ethoxyÂ  carboxylateÂ  with aÂ  linear hydrophobic structure.Â  This surfactant produces a high incremental oil recovery according to Berea core flood tests. The AN2NS and AN3 surfactants recovered 90% and 86% of OOIP respectively.